The IS curve and the transmission of monetary policy: Is there a puzzle? - Charles A. E. Goodhart; Boris Hofmann (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2003)
In this paper we assess the performance of the New Keynesian IS Curve for the G7 countries. We find that there is an IS puzzle for both the purely backwardlooking as well as for the forward-looking IS curve. The real interest rate does not have a significantly negative effect on the output gap. Based on an extended specification of the IS curve, also including asset prices and monetary aggregates, we are able to restore a significantly negative interest rate effect on aggregate demand in all countries. This finding suggests that a richer specification of the IS curve in empirical work may be necessary in order to obtain an unbiased estimate of the effect of monetary policy on aggregate demand.
Keywords: 330; IS-LM-Diagramm; Ungleichgewichtstheorie; Transmissionsmechanismus; Phillips-Kurve; Schätzung; G-7-Staate